Pedagogical technology in professional-practical physical training of students of the faculty of military education - Hasanov A.T. ,; Akzamov S.D.,; Abduraimov D.T. , (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article examines the issues of introducing pedagogical technologies for professional-practical physical training into the educational process in the training of specialists in military education before conscripts in the faculties of military education of higher humanitarian educational institutions.